Characterization of organic compounds in biochars derived from municipal solid waste. (September 2017) - Taherymoosavi, Sarasadat; Verheyen, Vince; Munroe, Paul; Joseph, Stephen; Reynolds, Alicia
Highlights: Biochar from municipal solid waste can manage waste and improve soil fertility. Municipal solid waste biochars, produced at three temperatures, were characterized. Pyrolysis temperature changed the type and concentration of the organic compounds. Mineral phases interacted with organic compounds at higher pyrolysis temperatures. Abstract: Municipal solid waste (MSW) generation has been growing in many countries, which has led to numerous environmental problems. Converting MSW into a valuable biochar-based by-product can manage waste and, possibly, improve soil fertility, depending on the soil properties. In this study, MSW-based biochars, collected from domestic waste materials and kerbsides in two Sydney's regions, were composted and pyrolysed at 450 °C, 550 °C and 650 °C. The characteristics of the organic components and their interactions with mineral phases were investigated using a range of analytical techniques, with special attention given to polycyclic aromatic hydrocarbons and heavy metal concentrations. The MSW biochar prepared at 450 °C contained the most complex organic compounds. The highest concentration of fixed C, indicating the stability of biochar, was detected in the high-temperature-biochar. Microscopic analysis showed development of pores and migration of mineral phases, mainly Ca/P/O-rich phases, into the micro-pores and Si/Al/O-rich phases on the surface of the biochar in the MSW biochar produced at 550 °C. Amalgamation of organic phases with mineral compounds was observed, at higher pyrolysis temperatures, indicating chemical reactions between these two phases at 650 °C. XPS analysis showed the main changes occurred in C and N bonds. During heat treatment, N-C/C=N functionalities decomposed and oxidized N configurations, mainly pyridine-N-oxide groups, were formed. The majority of the dissolved organic carbon fraction in both MSW biochar produced at 450 °C and 550 °C was in the form of building blocks, whereas LMW acids was the main fraction in high-temperature-biochar (59.9%).